4.6 BEAT-BY-BEAT ASSESSMENT OF CARDIAC AFTERLOAD USING AORTIC PU LOOP – A PILOT STUDY - Arthur Le Gall; Jona Joachim; Joaquim Mateo; Alexandre Mebazaa; Etienne Gayat; Fabrice Vallée (Artery Research, 2016)
Purpose/Background/Objectives: Cardiac afterload evaluation is crucial during general anesthesia (GA) especially during hypotension episode. Using beat to beat aortic pressure (P) / flow velocity (U) loop constructed from routine signals recorded during GA might allow to track afterload changes. Methods: We defined 3 angles characterizing the PU loop (alpha, beta and Global After-Load Angle (GALA) angles). Augmentation index (AIx) and total arterial compliance (Ctot) were also measured via radial tonometry and transfer function. Twenty patients were recruited and classified into low and high cardiovascular (CV) risk group. Vasopressors were administered, when baseline mean arterial pressure (MAP) fell by 20%. Results: We studied 118 pairs of pre/post bolus measurements. At baseline, patients in the lower CV risk group had higher cardiac output (6.1±1.7 vs 4.2±0.6 L/min meanSD p<0.001), higher Ctot (2.7±1.0 vs 2.0±0.4 ml/mmHg p<0.001), lower AIx (13±10 vs 32±11 % p<0.001) and lower GALA (41±15 vs 68±6 ° p<0.001). GALA was associated with Ctot and AIx. After vasopressors, MAP increase was associated with a decrease in Ctot (2.4±0.9 vs 1.7±0.7 ml/mmHg p<0.001), and an increase in AIx (21±14 vs 25±14 % p<0.001) and GALA (53±18 vs 61±16 ° p<0.001). Changes in GALA and Ctot after vasopressors were strongly associated (p=0.004). Conclusions: PU Loop assessment from routine hemodynamic optimization management during GA and especially our novel GALA parameter could monitor cardiac afterload continuously in anesthetized patients, and may help clinicians to titrate vasopressor therapy.